Building with buildings: an investigation of the demolition stock in Sweden and how these buildings could be turned into resources again - Nygren, Linnea (My University, 2022)
In Sweden we use resources four times beyond our planetary boundaries. One of the reasons are that objects, goods and even buildings are treated as if they were disposables that become waste and gets demolished when they are not useful or wanted anymore. The building industry stands for 45% of Sweden’s resource extraction, 40% of our amount of greenhouse gas emissions and 40% of our waste production. This a cycle of events that could be decreased remarkably if already built buildings were treated as resources and material banks instead of being crushed through demolition when they are not wanted anymore. Against this background following questions are asked: Q1: What type of buildings are being demolished in Sweden? Q2: What are the aspects that could enable an industrial reuse of building elements in new construction? Q3: How could building elements from the demolition stock in Sweden be turned into resources suitable to use in new construction in a systematic way? To answer these questions the thesis is mapping demolition permits from three municipalities in Sweden showing both types, the amount, and local characteristics of the demolition. Through literature studies, reference studies and interviews the thesis investigates how these found resources can be used. It discusses what the major differences are with a reuse project compared to conventional new construction and what the aspects are that could enable an industrial reuse in practice. Findings are that the biggest difference is the reliability on the resources and the amount of labour that is needed to ensure them . The reliability concerns both the supply and the difficulties in ensuring technical aspects. The suggested answer to found problems, possibilities, and resources is a general design proposal with a loadbearing wooden construction that use reused building elements as filling. This is tested through a redesign of a multifamily building in Gothenburg examining the impact on expression, floorplan, and overall layout of the building.
Keywords: Circularity, Deconstruction, Demomlition, Reuse